A Case Study on the Impact of Industrial Development on Urban Landuse in Ayutthaya, Thailand - Janya, Lakana (2004)
In the past decade, rapid growth of Thailand’s economy has affected the pattern of land usage in Ayutthaya city. Large agricultural land areas had become golf courses, garden homes, housing areas and industrial estates. This is a result of booming land prices between 1985 to 1990 which has encouraged land owners to sell their land at prices higher than the real value. In addition, from 1991, an industrial development policy has made Ayutthaya as an industrial area and this move has affected the pattern of land usage, land utilization and bring about problems such as national forest reserve encroachment, demolishment of historical heritage, environmental pollution, transportation as well as social problems. This study focuses on the impact of industrial development on urban land usage in Ayutthaya, Thailand. The study aims to investigate the pattern of land usage, analyse the rate of change on land utilization and determine the effect of industrial development on land usage and quality of life. The data were collected using questionnaires and secondary resources. The study covered Ayutthaya province in three areas; Phra Nakhon Si Ayutthaya, Sena and Uthai. The sample frame includes people who are involved in agricultural and industrial sectors in Ayutthaya. The sample size included members from 500 households. The data were analysed using SPSS program and statistical analysis such as ANOVA, regression, chi-squre, and t-test were used for hypotheses testing. The findings showed that land were used in two different ways in Ayutthaya; (1) farm holding land which is used for agriculture and rearing livestock, and (2) land which is used for residential, business, commercial, and industrial activities. The rate of change for land utilization indicated that the amount of agricultural areas are decreasing due to the establishment of industrial estates, increasing number of factories and changes to the land usage pattern. Lastly, industrial development is also affecting the lifestyles of the surrounding population.